DAMPAK DARI PROFESIONALISME GURU TERHADAP KINERJA GURU SMA SWASTA SULTAN AGUNG PEMATANG SIANTAR - Ernest Grace; Kevin Indajang; Efendi Efendi; Sudung Simatupang (LPPM Institut Pendidikan Nusantara Global, 2023)
The purpose of this study was to determine the effect of teacher professionalism variables on teacher performance at Sultan Agung Pematng Siantar Private High School totaling 41 teachers, consisting of Foundation Permanent Teachers and Foundation Non-Permanent Teachers. The results of the questionnaire distribution show that the research instrument for the variables of teacher professionalism and teacher performance has valid and reliable criteria, with the condition that the research variables have a normal distribution due to asymp values. Sig. (2-tailed) of each variable ≥ α 0.05. The results of the coefficient determination showed that the ability of professional variables to teacher performance was 0.54 or 54%, and had a strong correlation. For the regression equation, it shows the value of the equation Y = 18.442 + 1.739, which means that there is an influence of a positive direction coefficient of professionalism on teacher performance variables in Sultan Agung Pematang Siantar Private High School Teachers. The results of the hypothesis show that there is an influence of a positive direction coefficient of professionalism on teacher performance variables in Sultan Agung Pematang Siantar Private High School Teachers.